2013
DOI: 10.1590/s0100-736x2013001200002
|View full text |Cite
|
Sign up to set email alerts
|

Cellular immune response of Curraleiro Pé-duro and Nellore calves following Mycobacterium bovis-BCG vaccination

Abstract: The present study aimed to assess the CD4, CD8 and γδ blood levels for Curraleiro Pé-duro, as well as the specific IFN-γ response after BCG vaccination using flow cytometry. The specific immune response against BCG was also evaluated by tuberculin skin test, performed before and 45 days after the vaccination. For comparison purposes, the same parameters were investigated on Nellore calves, an exotic bovine with resistance previously demonstrated. Naturally, Curraleiro Pé-duro animals had greater levels of CD4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…A better cellular response was also observed in Curraleiro calves compared to Nellore animals, measured as the yeast phagocytosis ability as well as homogenous and sustained production of nitric oxide (a microbicidal substance) by macrophages derived from peripheral blood mononuclear cells in response to a vaccine. The lymphocyte cytometric analysis demonstrated that Curraleiro calves had more Tγδ cells; furthermore, CD4, CD8, and IFN-γ production by CD4 and CD8 T cells was found to be more efficient in Curraleiro animals, specifically and non-specifically (Maggioli et al 2013).…”
Section: Tuberculosismentioning
confidence: 93%
“…A better cellular response was also observed in Curraleiro calves compared to Nellore animals, measured as the yeast phagocytosis ability as well as homogenous and sustained production of nitric oxide (a microbicidal substance) by macrophages derived from peripheral blood mononuclear cells in response to a vaccine. The lymphocyte cytometric analysis demonstrated that Curraleiro calves had more Tγδ cells; furthermore, CD4, CD8, and IFN-γ production by CD4 and CD8 T cells was found to be more efficient in Curraleiro animals, specifically and non-specifically (Maggioli et al 2013).…”
Section: Tuberculosismentioning
confidence: 93%
“…The first gene belongs to the β-defensin family, which are antimicrobial peptides contributing to host defense during infection by acting against many unicellular parasites (Brogden, 2005;Lehrer et al, 1993;Nicolas & Mor, 1995) and are responsible for inducing primary immunological responsiveness (Banchereau et al, 2000;Sakaguchi et al, 2008). The potential of Brazilian locally adapted cattle breeds responsiveness was demonstrated by Maggioli et al (2013). The TRBV3-1 gene is closely associated with T lymphocytes and T-cell response, playing a central role in the adaptive immune response.…”
Section: Correspondence Analysismentioning
confidence: 99%
“…Curraleiro Pé-Duro (CPD) is a local Brazilian bovine breed with historical, cultural, and ecological values, but its population size is small and faces the risk of extinction [1]. The breed is rustic and shows high resistance to regional endemic diseases [2] because of the high level of circulating T-lymphocytes, which decreases with age. Besides, it has high levels of lymphocytes, which give the breed resistance to hemoparasitosis [3], Mycobacterium bovis, and other infections [2].…”
Section: Introductionmentioning
confidence: 99%